PGPR BIOSTIMULANTS AS EFFECTIVE DROUGHT MITIGATING AGENTS - Tariq, Aqsa; Ahmed, Ambreen; Abdullah, Humera (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Drought is severe environmental stress effecting the agriculture sector on a large scale. Plants under drought have shown low productivity, however, Plant growth promoting rhizobacteria (PGPR) have ability to enhance plant tolerance and maintain their water potential status. In current study highly drought tolerant exopolysaccharides (EPS) producing rhizobacteria are used and their phytostimulatory activity have been observed using Triticum aestivum. Three levels of water stress (normal, moderate and severe drought stress conditions) have been maintained firstly by increasing solute concentration in soil and secondly by varying watering intervals. Growth parameters and biochemical analysis of bacterized Triticum aestivum was carried out and compared with non-treated plants. All bacterial strains used in current studies i.e., Pseudomonas sp. (DS1), Shewanella putrefaciens (DS2), Pseudomonas sp. (DS3), Pseudomonas aeruginosa (DS4) and Pseudomonas sp. (ES2) shave shown array of varying behavior. These PGPR have shown better results under stress condition provided by varying water intervals as compared to the stress provided by increasing solute concentration, though, improvement have been observed in all cases. Hence, these PGPR can be used as biostimulants in agriculture fields to improve crop quality and productivity.